Development and Characterization of recombinant immunotoxins for cervical carcinoma - Henry, Marc (Institute of Infectious Disease and Molecular Medicine, 2024)
Cervical cancer is the second most frequent occurring cancer in South African women. Cervical cancer accounts for 41.7% of all cancer in black women and 37% in coloured women. If detected early the disease can be treated, however patients are only diagnosed once the cancer has reached its advanced stages. This poor outcome is due to personal reasons of the patient, lack of screening facilities or lack of education. Cervical cancer is a consequence of Human papillomavirus (HPV) infection. Whereby the virus infects epithelial cells of the cervix and integrates its viral DNA into the host's genome. The viral DNA encodes oncogenes and initiates various pathways within the cells to undergo oncogenesis. During oncogenesis the cells protrude various surface receptors to ensure growth and survival of the cancerous cells. Through many cycles of uncontrolled cell proliferation, the cancer will eventually form a tumour in the cervix, this usually occurs during the advanced stages of cervical cancer. Once the cancer has reached advanced stages current treatment has very limited therapeutic effect. This is due to the cancers' ability to develop resistance against current treatments i.e., chemoresistance which leads to a relapse. Therefore, the demand for novel therapeutics for treating advanced stage cancers are high. Immunotoxins are fusion proteins that consist of an antibody that binds specifically to the cancer cell connected to a protein toxin capable of killing the cell. Immunotoxins have proven to be a promising alternative to current treatment for cancer. Immunotoxins utilize the ability of antibodies to target cancerous cells without affecting the healthy cells due to certain surface receptors being overexpressed in cancerous cells and not in healthy cells. Studies have shown that cell surface receptors LGR5, EpCAM and CD90 are overexpressed in cervical carcinoma. Full length antibodies have been proven to be less effective when used against tumours whereas, various formats of antibody such as fragment antigen binding (Fab) and single chain variable fragment (scFv) demonstrated greater penetration properties. Pseudomonas exotoxin A (ETA) is a highly cytotoxic enzyme that modifies elongation factor 2 of the cell. This modification is irreversible and arrests protein synthesis thereby causing cell death. ETA is prone to causing a humoral response within patients. This unwanted effect can be prevented by introducing point mutations into the ETA gene. The point mutations are to reduce the chances of an immune response from occurring whilst maintaining the cytotoxic activity of the wildtype (wt) ETA. This study aims to produce scFv antibodies targeting the MSc Thesis - 13 - Marc Henry three overexpressed biomarkers found in cervical carcinoma connected to a wt ETA or a mutant variant generated from computer simulation by our collaborating partner Prof Paolo Carloni (Forschungszentrum Julich, Germany) described as de-immunised (dETA). The recombinant immunotoxins (rITs) were generated by designing a bacterial periplasmic expression plasmid containing ETA or dETA to be fused to a scFv antibody fragment targeting one of the three biomarkers (LGR5, CD90 and EpCAM). The corresponding scFv was cloned into this plasmid before being transformed into Escherichia coli (E. coli) BL21. The periplasm of E. coli BL21 was used to produce the rITs by performing bacterial expression under osmotic stress conditions. The rITs were purified using immobilized metal affinity chromatography (IMAC) and size exclusion chromatography (SEC). Purified proteins were characterized by sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS PAGE) and western blot analysis. Once expression of full-length proteins was confirmed the rITs were assessed on the cervical carcinoma cell line CaSki for binding and cytotoxicity studies. The results demonstrate that the periplasm of the E. coli BL21 can be utilized to generate complex fusion proteins, this being evidenced by the SDS PAGE and western blot results. Both ETA and dETA rITs exhibited strong binding towards CaSki cells. The cytotoxicity assays indicate that both ETA and dETA rITs are capable of targeted killing. However, ETA seems to demonstrate a more potent response compared to the dETA. This may be due to the computer simulated mutant R456T not being able to fully recover the enzymatic activity of B cell epitope depleted dETA to its original wt activity. The result of this study showcases that this form of treatment may potentially be effective treatment for patients experiencing advanced stages of cervical cancer. However, in future studies other cervical cancer lines should be assessed and eventually patient samples should be assessed in binding and cytotoxicity studies. Although this dETA variant seems to possess a lower potency compared to wildtype ETA immunogenicity analysis using mouse models to determine whether the dETA variant reduces the humoral response within the host would be essential.